KONSEP DASAR EMBRIOLOGI: TINJAUAN TEORETIS - HAVIZ, M. (IAIN Batusangkar, 2014)
Embryology is part of a study of developmental biology. In embryology widely used terms that will clarify a process, and the state or the name of a body part, such as teratology, is part of a study of embryology and cause birth defects. Fetuses and embryos as another name for the developing fetus. Individual development process involves five kinds of processes, namely the growth, differentiation, cellular interactions, movement and metabolism. The fifth process will always be found in every stage of human development (day after day and week after week). Embryology process closely related to the presence and action of genes in the body. Advances in technology have shown that the lack of regulation in the body at the cellular level is called the molecular regulation and signaling. Key words ; embryology, developmental of biology